树舌发酵浸膏饲料添加剂 (2018)
本发明公开了树舌发酵浸膏饲料添加剂，它是树舌菌株经接种、摇瓶培养、种子罐发酵；发酵液经95-100℃蒸煮，过滤，滤液浓缩成的浸膏；在饲料中添加了0.05-0.2%上述的树舌发酵浸膏能够提高肉鸡日增重，提高饲料转化率，促进动物生长；同时还能调节肉鸡盲肠肠道菌群，降低鸡肉中胆固醇含量,此外,还能显著提高肉鸡的免疫功能及肠黏膜免疫功能。效果优于添加黄霉素，原料廉价易得，无毒付作用，解决了饲料中添加抗菌素产生耐药菌的问题。 The present invention discloses a ganoderma applanatum fermented extract paste feed additive. The ganoderma applanatum fermented extract paste is obtained by ganoderma applanatum strain inoculating, shake flask culturing, seed tank fermenting, and fermentation broth steaming and cooking at 95-100 DEG C and filtering, and filtrate concentrating. 0.05-0.2% of the ganoderma applanatum fermented extract paste added in feed can improve the daily weight gain of broiler chickens and feed conversion rate, promote animal growth, at the same time adjust the intestinal flora of broiler chicken caecum and reduce cholesterol levels in chicken meat. In addition, the ganoderma applanatum fermented extract paste feed additive can also significantly improve immune function and intestinal mucosal immune function of broil